2020
DOI: 10.4317/jced.56289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of desmoglein 1 and 3 autoantibodies in pemphigus vulgaris: correlation with disease severity

Abstract: Background: Pemphigus is an autoimmune blistering disease of the skin and mucous membranes caused by autoantibodies against desmoglein 1 (Dsg1) and desmoglein 3 (Dsg3). Pemphigus vulgaris (PV) is the most common form of pemphigus. The aim of this study was to assess the correlation between the levels of anti-desmoglein 1 and 3 autoantibodies and the severity of PV disease. Material and Methods: Nineteen newly diagnosed patients with pemphigus vulgaris were enrolled in this study. The titers of Dsg in subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…A previous study suggested that anti-desmoglein-1 autoantibody titers seem to be more useful in showing the extent of the disease and pemphigus activity with mucocutaneous lesions. In contrast, antidesmoglein-3 autoantibody titers can be used for diagnostic purposes [21].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that anti-desmoglein-1 autoantibody titers seem to be more useful in showing the extent of the disease and pemphigus activity with mucocutaneous lesions. In contrast, antidesmoglein-3 autoantibody titers can be used for diagnostic purposes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The studies were conducted in 20 countries: Argentina, 7 Brazil, 15,16 Croatia, 17 Egypt, 18 Greece, 19 India, 6,20–23 Iran, 24–29 Italy, 2,3,30 Japan, 31 Korea, 32 Kuwait, 33 Macedonia, 34 Mexico, 35 Morocco, 8,36 Romania, 37 Serbia and Montenegro, 38 Slovakia, 39 Spain, 40,41 Thailand, 42 and Turkey 1,5,9,43–45 . Years of publication ranged from 1999 33 to 2020 3,4,6–9,24 .…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in 20 countries: Argentina, 7 Brazil, 15,16 Croatia, 17 Egypt, 18 Greece, 19 India, 6,20–23 Iran, 24–29 Italy, 2,3,30 Japan, 31 Korea, 32 Kuwait, 33 Macedonia, 34 Mexico, 35 Morocco, 8,36 Romania, 37 Serbia and Montenegro, 38 Slovakia, 39 Spain, 40,41 Thailand, 42 and Turkey 1,5,9,43–45 . Years of publication ranged from 1999 33 to 2020 3,4,6–9,24 . The most common study design was observational study as retrospective reviews ( n = 20, 50%), followed by retrospective studies with follow‐up ( n = 18, 45%), and two prospective studies (5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical manifestation is due to the difference in timing of the presence of antibodies against Dsg 1 and Dsg 3. Several studies have shown that Dsg 3 antibodies were identified in 90–98% of all patients at the time of the initial diagnosis, while positive Dsg 1 antibodies were detected in only 63% of patients with PV at the time of diagnosis [ 13 ]. The clinical significance of this pathophysiological process in PV development explains the diagnostic delay: since around 60–80% of patients experience oral lesions first, and the disease remains limited to mucosal surfaces in 1 in 4 patients, diagnostic delays are commonly observed in PV [ 14 ].…”
Section: Clinical Presentationmentioning
confidence: 99%